Methodological instructions for practical classes in English language - Khramtsova, T. O.; Khaziyev, A. V. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The purpose of these guidelines is to develop students' skills in performing English language test tasks in such areas as reading, vocabulary, grammar, oral and written language use, and to help them prepare for the exam. The guidelines are designed to prepare bachelor's degree students. They meet the requirements of the Bachelor's language training programme for the English language exams in the test form in the areas of reading, vocabulary, grammar, oral and written language use. The materials of the guidelines are structured and allow students to objectively assess their readiness to perceive information in a foreign language both orally and in writing. They include the latest teaching materials on modern achievements in certain aspects of science and technology, which encourages students' learning and motivates them. The guidelines consist of 4 main parts, each of which is divided into 2 parts: grammar (multiple-choice tasks) and language use (filling in the gaps in the text); reading (tasks to determine the correctness of statements). Each task contains instructions, a text and questions or statements to the text. The material used was authentic literature and original popular science texts.
Keywords: methodological instructions; practical classes; English language; indirect speech; nouns; quantifiers